The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2019
DOI: 10.1371/journal.pone.0214246
|View full text |Cite
|
Sign up to set email alerts
|

Prior cigarette smoke exposure does not affect acute post-stroke outcomes in mice

Abstract: Chronic obstructive pulmonary disease (COPD) is currently the third leading cause of death globally and is characterized by airflow limitation that is progressive and not fully reversible. Cigarette smoking is the major cause of COPD. Fifty percent of deaths in the COPD population are due to a cardiovascular event and it is now recognised that COPD is a risk factor for stroke. Whether COPD increases stroke severity has not been explored. The aim of this study was to investigate whether functional and histologi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 38 publications
(52 reference statements)
1
1
0
Order By: Relevance
“…Consistent with our previous studies 33,34 , we found in this study that mice exposed to CS had a significant increase in total inflammatory cells in the BALF, which was largely attributed to increased macrophages and neutrophils. Human studies have also shown that COPD patients have increased macrophages in BALF, sputum, airways and lung parenchyma compared to healthy individuals 2 .…”
Section: Discussionsupporting
confidence: 93%
“…Consistent with our previous studies 33,34 , we found in this study that mice exposed to CS had a significant increase in total inflammatory cells in the BALF, which was largely attributed to increased macrophages and neutrophils. Human studies have also shown that COPD patients have increased macrophages in BALF, sputum, airways and lung parenchyma compared to healthy individuals 2 .…”
Section: Discussionsupporting
confidence: 93%
“…It's notable that the influences of cigarette smoke on stroke severity may be affected by the length of exposure duration and exposure dose. A recent study reported that cigarette smoke exposure at a dose of nine cigarettes per day had no significant impact on brain infarction or neurological deficits in mice subjected to 30–40 min MCAO (32). The reasons that caused this discrepancy may be at least partially caused by the different exposure protocol of cigarette smoke and ischemia duration.…”
Section: Discussionmentioning
confidence: 99%